Bosentan for Treatment of Pediatric Idiopathic Pulmonary Arterial Hypertension: State-of-the-Art - Wang, Yuchen; Chen, Selena; Du, Junbao (Frontiers in Pediatrics, 2019)
Idiopathic pulmonary arterial hypertension (IPAH) is a complex disease associated with progressive deterioration. Targeted therapy for IPAH has improved in the last several decades. However, there remain many challenges to current treatment of children with IPAH, including poor prognosis and a median survival of 0.8 years. Endothelin-1 (ET-1) appears to be a key mediator in the pathogenesis of IPAH, with elevated concentrations in the plasma. Bosentan, an endothelin receptor antagonist, has been confirmed in Food and Drug Administration (FDA) to effectively treat IPAH when administered in recent studies. This review focuses on related studies and advance of bosentan in the treatment of IPAH in children.